Effects of atrial fibrillation on prognosis of acute myocardial infarction. Issue 3 (March 1978) - Hunt, D; Sloman, G; Penington, C
Abstract : Nine hundred and sixty-nine coronary care patients with acute myocardial infarction were followed for one year. Atrial fibrillation was documented in 107 patients. Compared with patients without atrial fibrillation, those with this arrhythmia were older, had clinically more severe infarction, and had a higher frequency of ventricular fibrillation or tachycardia, and right bundle-branch block. They had similar past histories of ischaemic heart disease and coronary risk factors. Patients with atrial fibrillation had a higher total mortality at 3 months and 12 months. The presence of atrial fibrillation was not associated with any significant increase in mortality within any decade of age or within any subgroup of clinical severity of infarction. The frequency of atrial fibrillation was similar in anterior and inferior infarction. Multiple episodes of atrial fibrillation occurred in 52 patients and episodes usually lasted for over 1 hour. In 50% of patients with single episode of atrial fibrillation the initial ventricular rate was greater than 120 beats per minute.